Studi Kinerja Ruas Jalan Arteri Terhadap Pengaruh Hambatan Samping Pada Ruas Jalan Yos Sudarso di Kota Tarakan - Zultan M, Achmad; Kamsiah, Kamsiah (Jurusan Teknik Sipil, 2018)
Side friction is a towards the flow roadway at an internode road which is able to cause a conflict and has big effect for the activities in roadway. Side frictions which were effected the capacity and pedestrians in city road were pedestrians, transportations which stopped, slow transportations (bicycle, wheelborrow, etc) and transportations which were went in and out from the side internode road. The purpose of this research is to find out the significant effect of side friction toward the road performance. After several stages in collecting the data and data analysis using method (MKJI 1997), it can be concluded that the effect of side friction toward the performance at Yos Sudarso street for the relation between road volume with side friction which has the highest correlation score was transportations which were went in and out at 0,260. Meanwhile, the relation of rapidity transportations with side friction which has the highest correlation score was the transportations which stopped at 0,495. The factor that effected the internode performance at Yos Sudarso was the side friction which has the highest score after the transportations which went in and out started at 17.00 – 18.00pm, so the total was 1.278,90.